Citrus Tristeza Virus: Making an Ally from an Enemy - Dawson, William O.; Bar-Joseph, Moshe; Garnsey, Stephen M.; Moreno, Pedro (2017)
Virus diseases of perennial trees and vines have characteristics not amenable to study using small model annual plants. Unique disease symptoms such as graft incompatibilities and stem pitting cause considerable crop losses. Also, viruses in these long-living plants tend to accumulate complex populations of viruses and strains. Considerable progress has been made in understanding the biology and genetics of Citrus tristeza virus (CTV) and in developing it into a tool for crop protection and improvement. The diseases in tree and vine crops have commonalities for which CTV can be used to develop a baseline. The purpose of this review is to provide a necessary background of systems and reagents developed for CTV that can be used for continued progress in this area and to point out the value of the CTV-citrus system in answering important questions on plant-virus interactions and developing new methods for controlling plant diseases.